2016
DOI: 10.1186/s12936-016-1141-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax mdr1 genotypes in isolates from successfully cured patients living in endemic and non-endemic Brazilian areas

Abstract: BackgroundPlasmodium vivax is the most widely distributed species causing the highest number of malaria cases in the world. In Brazil, P. vivax is responsible for approximately 84 % of reported cases. In the absence of a vaccine, control strategies are based on the management of cases through rapid diagnosis and adequate treatment, in addition to vector control measures. The approaches used to investigate P. vivax resistance to chloroquine (CQ) were exclusively in vivo studies because of the difficulty in keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
4
12
1
Order By: Relevance
“…Our study, by thoroughly characterizing these regions (that were very incompletely annotated previously), also provides an important resource to better investigate the role of these regions and their variability. One gene that would be interesting to further study based on our findings is PvMDR1, which is commonly duplicated in some endemic regions 34 and has been implicated in chloroquine or mefloquine resistance 35 , 36 . Our data clearly indicated the presence of alternatively spliced 3′-UTR introns in some transcripts, and it would be interesting to test whether these isoforms affect PvMDR1 translation or are associated with antimalarial drug resistance.…”
Section: Discussionmentioning
confidence: 90%
“…Our study, by thoroughly characterizing these regions (that were very incompletely annotated previously), also provides an important resource to better investigate the role of these regions and their variability. One gene that would be interesting to further study based on our findings is PvMDR1, which is commonly duplicated in some endemic regions 34 and has been implicated in chloroquine or mefloquine resistance 35 , 36 . Our data clearly indicated the presence of alternatively spliced 3′-UTR introns in some transcripts, and it would be interesting to test whether these isoforms affect PvMDR1 translation or are associated with antimalarial drug resistance.…”
Section: Discussionmentioning
confidence: 90%
“…These temporal variations of allele frequencies could be explained by different factors, such as the increased circulation of isolates between French Guiana and Brazil or changes in drug policy for the treatment of P. falciparum . This is supported by a recent study showing that the T958M mutation allele is the majority among Brazilian isolates collected between 2010 and 2014 [42]. Many studies in Southeast Asia have shown that isolates with pvmdr1 gene amplification were characterized by increased susceptibility to chloroquine but decreased susceptibility to mefloquine [13, 31].…”
Section: Discussionmentioning
confidence: 72%
“…Analysis of pvmdr1 sequences has shown SNPs at three codons 958, 976 and 1076 as previously described [ 6 , 12 , 15 , 17 , 19 ]. The substitution in the codon T958 M is known as an allelic variant, of which T958 wild-type was identified in Ecuador and 958M is thought being characteristic of Asia and Africa [ 12 ], while it has also been found in samples from Brazil [ 19 ]., The allelic form 958M was identified in samples from Africa and south western Asia tested here. Few isolates showed the single mutation Y976 F (4/30), in agreement with the fact that the single 976 F mutant is not very common worldwide [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The substitution in the codon T958 M is known as an allelic variant, of which T958 wild-type was identified in Ecuador and 958M is thought being characteristic of Asia and Africa [ 12 ], while it has also been found in samples from Brazil [ 19 ]., The allelic form 958M was identified in samples from Africa and south western Asia tested here. Few isolates showed the single mutation Y976 F (4/30), in agreement with the fact that the single 976 F mutant is not very common worldwide [ 17 , 19 ]. In contrast, many studies have reported a high prevalence of the Y976 L and/or F1076 L mutants associated with treatment failure [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation